Acute obstructive suppurative pancreatic ductitis in pancreatic malignancies - Shimizuguchi, Ryoko; Kikuyama, Masataka; Kamisawa, Terumi; Kuruma, Sawako; Chiba, Kazuro (Endoscopy International Open, 2020)
Background and study aims Acute obstructive suppurative pancreatic ductitis (AOSPD) is a suppurative pancreatic duct infection with main pancreatic duct (MPD) or accessory pancreatic duct obstruction in the absence of a pancreatic pseudocyst or necrosis, which is experienced usually in chronic pancreatitis. The diagnosis is confirmed by the finding of pancreatic duct obstruction on endoscopic retrograde cholangiopancreatography (ERCP) with evidence of infection, such as a positive pancreatic juice culture or drainage of purulent pancreatic juice.Patients and methods We studied five patients with pancreatic ductal adenocarcinoma (PDAC) and one with chronic myelogenous leukemia (CML), who suffered from AOSPD.Results Of the 281 PDAC and 39 CML patients who we treated in the past 2 years in our hospital, five with PDAC (1.8 %) and one with CML (2.6 %) experienced AOSPD. Each patient had fever, abdominal pain, and increased blood C-reactive protein. Pancreatography found that each patient had a MPD stricture and an upstream dilatation. Four had a disruption of the MPD in the upper stream of the stricture. Nasopancreatic drainage was successfully performed in all patients. Pancreatic juice culture was positive for Klebsiella pneumonia, Enterobacter agerogenes, or Enterococcus cloacae in four patients.Conclusion AOSPD should be considered in pancreatic malignancy with fever and abdominal pain. Prompt diagnosis of AOSPD could avoid shortening of survival of patients with an already poor prognosis by infection.